Behavioural and chemoreceptor cell responses of the tick, Ixodes ricinus, to its own faeces and faecal constituents - Grenacher, Stoyan; Kröber, Thomas; Guerin, Patrick; Vlimant, Michèle (Springer, 2001)
Ticks are ectoparasites of vertebrates and utilize a variety ofinfochemicals for host finding and acceptance as well as for intraspecific aggregation and mating responses. Individual male and female Ixodes ricinus, the vector of Lyme disease in Europe, readily arrest onfilter paper strips contaminated with their own faeces. I. ricinus also responds, but to a lesser degree, tofaeces-contaminated papers enclosed in metal mesh envelopes, i.e. without directly contacting the faeces, suggesting a role for volatiles in the arrestment response. The faecal constituents guanine, xanthine, uric acid and 8-azaguanine (a bacterial breakdown product of guanine) also caused arrestment of individual I.ricinus males and females. However, mixtures of these products induced arrestment of I. ricinus at doses one hundred fold lower than the lowest active dose of any of them tested singly. Saline extracts of faeces activated receptor cells in terminal pore sensilla on the first legtarsi of I. ricinus. One cell in these sensilla responded in a similar dose dependent manner to guanine and 8-azaguanine, whereas a second cell was more sensitive to lower doses of 8-azaguanine. The response threshold approached 100 fM for both cells. These findings suggest that faeces and faecal breakdown products are implicated in aggregation responses of I. ricinus. This may account for the clumped distribution of this ectoparasite on the ground and contribute to the high proportion of mated individuals recorded prior to host colonization.
Keywords: Aggregation pheromone; Behaviour; Chemosensilla; Guanine; Gustation; Ixodes ricinus; Purines; Tick